Recent Progress in Nonlinear Frequency Conversion of Optical Vortex Lasers - Liu, Jie; Duan, Yanmin; Li, Zhihong; Zhang, Ge; Zhu, Haiyong (Frontiers in Physics, 2022)
Optical vortices are optical fields that possess a helical phase and orbital angular momentum, which have found the application in micromanipulation, optical communication, orbital angular momentum entanglement, super-resolution imaging, metrology, etc. The urgent need for the wide spreading applications of vortex lasers is to increase the wavelength versatility. In this study, the nonlinear frequency conversion of vortex lasers with a focus on sum frequency generation stimulated Raman scattering, and optical parametric oscillators were meticulously reviewed. The characteristics of the topological charge transfer and output beam profiles of different frequency conversion were discussed. As the precise tuning of optical fields in both temporal and spatial domains shall be the trend of future studies, it is our hope that this review shall serve as a reference for future research. Combining these techniques with the streaming methods to produce optical vortices, i.e., annular pump, off-axis pump, reflection mirror with defect spots, spherical aberration, and birefringence, it is advisable to expand the wavelength and fill the wavelength gap in the ultraviolet, visible, and infrared bands.